Experimental Study and Effect on Recycled Fibers Blended with Rotor/OE Yarns for the Production of Handloom Fabrics and Their Properties. (15th August 2021) - Awgichew, Dessalegn; Sakthivel, S.; Solomon, Eshetu; Bayu, Addisalem; Legese, Robel; Asfaw, Daniel; Bogale, Meseret; Aduna, Alemu; Senthil Kumar, S.
Abstract : The uses of recycled materials have gained massive importance in the textile sector and other application areas as the effects of reducing natural resources are felt worldwide. This study aimed to analyze the effects of recycled fiber usage on the properties of OE-rotor spun yarns and hand-woven fabrics produced from these yarns. For this purpose, OE-rotor yarns are produced at different proportion levels from virgin cotton and recycled fibers derived from knitted garment wastes at 25%, 50%, and 75%, respectively. For a better assessment, properties of OE-rotor yarns that contain recycled fibers and 100% virgin cotton OE-rotor yarns are compared. Physical, structural, and mechanical properties such as unevenness, imperfections, hairiness, breaking force, and elongation are analyzed by Uster Tester 5 SX, Uster Zweigle Hairiness Tester 5, and Uster Tensorapid 3. Plain and twill hand-woven fabrics are produced from OE-rotor spun yarns. Effects of recycled fiber proportion on hand-woven fabric properties such as pilling, abrasion resistance, and air permeability were also evaluated. Results showed that the use of up to 75% of recycled fiber cotton blended yarns shows no statistically significant differences in yarn and fabric properties.